A LITERATURE REVIEW STUDY ON SCHOOL EVALUATION FROM AN INCLUSIVE PERSPECTIVE - Gomes, Guadalupe Brandao de Souza; Rodrigues, Silvia Adriana [UNESP]; Giareta, Paulo Fioravante (Univ Federal Mato Grosso Sul, 2025)
This article is the result of a study whose general objective was to present a scenario of researchs developed in Brazil, at the master's and doctorate level, which discusses evaluation from an inclusive perspective, adopting a quantitative-qualitative, bibliographical, exploratory, research approach, of the state of knowledge type. The mapping of productions was carried out in the database of the Brazilian Digital Library of Theses and Dissertations (BDTD), without a time frame defined a priori, but taking into account the period referring to the publication of the works found and selected for the study in question, between the years 2006 and 2020. The quantitative analysis of the data shows a small number of investigations that discuss evaluation from an inclusive perspective. With regard to the qualitative examination, it was based on two categories: conceptions of school inclusion and conceptions of school assessment. In the first, there is a predominance of the concept of Education for All in regular schools, as well as Special Education when dealing with the relationship between inclusion and school evaluation. In the second category, the most recurrent conceptions of school assessment were: procedural or formative assessment, diagnostic assessment and mediating assessment. The scenario found showed that there is no work with the concept of school assessment assumed as a reference in this study, which is to create new ways of evaluating, as researcher Sandra Mara Corazza points out.
Keywords: School evaluation; School inclusion; Difference; Diversity; State of knowledge